2012
DOI: 10.1530/rep-12-0291
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin/Tcf signaling in murine oocytes identifies nonovulatory follicles

Abstract: WNTS are secreted glycoprotein molecules that signal through one of three signaling pathways. The best-characterized pathway involves stabilization of the multifunctional protein b-catenin, which in concert with members of the T-cell factor (Tcf) family activates specific gene transcription. We have examined putative Wnt/b-catenin in the murine ovary using transgenic mice harboring a reporter construct that activates b-galactosidase (lacZ) expression in response to b-catenin/Tcf binding (TopGal mice). Primordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
2
9
1
Order By: Relevance
“…Previously, we showed that quercetin inhibits the enzyme TG2 and its downstream intracellular signalling including the β-catenin pathway (Beazley et al 2012, 2013 a ), both of which have been implicated in fertility (Fujimoto et al 1996; Tulac et al 2003; Kabir-Salmani et al 2005; Fan et al 2010; Liu et al 2010; Usongo et al 2012; Wetendorf and DeMayo 2012). We therefore reasoned that if quercetin effects involved the inhibition of TG2 then quercetin supplement would not affect fertility in TG2-null female mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we showed that quercetin inhibits the enzyme TG2 and its downstream intracellular signalling including the β-catenin pathway (Beazley et al 2012, 2013 a ), both of which have been implicated in fertility (Fujimoto et al 1996; Tulac et al 2003; Kabir-Salmani et al 2005; Fan et al 2010; Liu et al 2010; Usongo et al 2012; Wetendorf and DeMayo 2012). We therefore reasoned that if quercetin effects involved the inhibition of TG2 then quercetin supplement would not affect fertility in TG2-null female mice.…”
Section: Resultsmentioning
confidence: 99%
“…Further, loss of TG2 attenuates quercetin effects on female reproduction observed in wild-type mice, in agreement with quercetin acting via inhibition of TG2. A plausible mechanism for the involvement of TG2 relates to its ability to activate the β-catenin signalling pathway (Beazley et al 2013 a ), which in the normal ovary is associated with non-ovulatory follicles (Usongo et al 2012) and can impair ovulation (Fan et al 2010). Therefore, it can be proposed that blocking TG2-mediated β-catenin signalling with quercetin (Beazley et al 2013 a ) may allow for enhanced ovulation; however, further studies will be necessary to directly establish the link between quercetin, TG2 and β-catenin in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slight variations in β-catenin amounts and/or its cellular localization have a profound effect on cell status. While functional studies indicate that Wnt/Wg signaling has a role in several aspects of ovarian function including folliculogenesis and steroidogenesis ( Boyer et al, 2010 ; Usongo et al, 2012 ), a number of questions regarding its functions in the germline remain open.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of miR-320 in mouse MII oocytes causes a decrease in the number of two-cell embryos and blastocysts, as well as an aberration in the expression of components of the WNT signaling pathway (Feng et al 2015). Though the WNT signaling pathways were studied in oocytes mainly in regard to early embryonic development, the canonical WNT signaling pathway is active in mouse oocytes from the stage of secondary follicle; its activity increases as the follicle grows, concomitantly with an increase in oocyte diameter, but it is undetectable in mature MII oocytes (Usongo et al 2012). Along with the possible role of WNT in modulating the actin cytoskeleton (Akiyama and Kawasaki 2006) and its cross talk with the PI3K/AKT signaling pathway (reviewed by Boyer et al 2010), it is of great interest to explore the involvement of miR-320 in oocyte maturation and emphasize its role as a regulator of WNT signaling.…”
Section: Oocyte Maturation and Early Embryogenesismentioning
confidence: 99%